1999
DOI: 10.1023/a:1008339709327
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The role of radiotherapy either as adjuvant or as primary treatment remains to be demonstrated in prospective randomised studies. From our results, it seems that high radiation doses could be dangerous and could detriment prognosis. Brachytherapy boost was not superior to treatment with external beam irradiation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Potential advantages of intraluminal BT include administration of high radiation doses with rapid dose fall-off over a short distance from the radioactive source, thus sparing adjacent normal tissues and localizing dose to the tumor and peritumoral tissues, although dose to extramural disease may also be limited. Some investigators have reported a correlation of improvement in survival with the use of BT (11), while others have shown no obvious benefit (15) (Table 4). Occasionally, reports have described long-term survival in unresectable patients with the use of EBRT and transcatheter BT boost.…”
Section: Discussionmentioning
confidence: 99%
“…Potential advantages of intraluminal BT include administration of high radiation doses with rapid dose fall-off over a short distance from the radioactive source, thus sparing adjacent normal tissues and localizing dose to the tumor and peritumoral tissues, although dose to extramural disease may also be limited. Some investigators have reported a correlation of improvement in survival with the use of BT (11), while others have shown no obvious benefit (15) (Table 4). Occasionally, reports have described long-term survival in unresectable patients with the use of EBRT and transcatheter BT boost.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no consensus has been established. Gonzalez Gonzalez et al suggested a dose >70 Gy because of the concept that CCA is a radio-resistant tumor 22. However, if radiation treatment with much higher dose caused serious toxicity that aborted treatment before completion, the patients would not benefit from adjuvant RT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, resection margin may have influenced survival outcomes. However, several studies reported that the effect of margin status on survival among patients with resected pCCA who received adjuvant chemoradiation therapy is minimal 22,25. The SEER database lacks its ability to capture margin status and chemotherapy regimens, but it seems to have little impact on this study.…”
Section: Discussionmentioning
confidence: 99%
“…McMasters et al [95] described a case series of nine patients with extrahepatic CC who were successfully down-staged with external beam radiotherapy: 100% had negative resection margins following surgery. However, in a longer term study by Gonzalez et al [96], which used combinations of pre- and post-operative external beam radiotherapy, no impact on one, three or five year survival was observed. More recently Gwak et al [97] observed a downward trend in five-year survival following adjuvant radiotherapy (21% vs. 11.6%).…”
Section: Treatment Of Locally Advanced and Metastatic CCmentioning
confidence: 98%